Organic soil fertility management practices for the management of fall armyworm, Spodoptera frugiperda (J.E. Smith), in maize - Bayissa, Wakuma; Abera, Asnake; Temesgen, Jibril; Abera, Gemechu; Mendesil, Esayas (Frontiers in Insect Science, 2023)
The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is native to the Americas and is a polyphagous pest that attacks several crops, but causes significant damage to maize, which is a staple crop in Africa. Organic soil amendments have an impact on physical, chemical and biological properties of soil, which enhances plant resistance or tolerance to insect pests and also promotes diversity of associated natural enemies of the pest. However, management practices of crop residue and animal manure affect their use as organic soil amendments. A field experiment was conducted to evaluate the effect of maize residue and cattle manure soil incorporation on FAW in the Mana and Omonada districts of the Jimma zone, southwestern Ethiopia, during the 2018/19 cropping seasons. Treatment involved three factors: Maize residue retention with five levels (0%, 25%, 50%, 75% and 100%), cattle manure storage system (control, open, steel roofed, and grass roofed stored manure) and two districts (Mana and Omonada) laid out in a randomized complete block design and replicated three times. The infestation and damage rating was collected from 30 days after planting within 20-day intervals. The results indicated that maize plots with retention of crop residues had significantly reduced FAW infestation compared to plots without maize residues (control) in both study districts. Furthermore, manure-fertilized plants had the lowest percentage of FAW infestation 10.8% of Mana and 22% of Omonada compared to maize plots without cattle manure both in Mana (37.3%) and Omonada (54.5%), respectivelyboth study districts. The lowest severity of FAW infestation (0.01) was recorded in a plot with 100% residue incorporated with cattle manure stored under a grass roof applied plot in the Mana district. Therefore, conventional tillage with 100% maize residue incorporation and application of cattle manure stored under a grass roof showed a better result in reducing FAW infestation in maize. However, further studies are important to determine the effect of treatments over seasons and locations on FAW infestation and maize yields.